2022
DOI: 10.1111/dom.14797
|View full text |Cite
|
Sign up to set email alerts
|

Prediabetes diagnosis is associated with the progression of coronary artery calcification: The Kangbuk Samsung Health Study

Abstract: Aim: To investigate the associations between prediabetes defined by different diagnostic criteria and coronary artery calcification (CAC) and its progression over time. Materials and Methods:This cross-sectional study included 146 436 Korean adults without diabetes who underwent CAC estimation computed tomography (CT) during health examinations from 2011 to 2019. We used multinomial logistic regression models. The longitudinal study comprised 41 100 participants with at least one follow-up cardiac CT and annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The evidence on the dose-response relationships between HbA1c and AC were limited. Previous researchers have found that higher HbA1c was independently associated with advanced AAC scores, CAC risk, and CAC progression [ 10 12 ], however, they did not investigate the dose-response relationships between HbA1c and these outcomes. The current study showed a nearly linear dose-response relationships between HbA1c and AAC, which provided evidence for preventing AC through reducing HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence on the dose-response relationships between HbA1c and AC were limited. Previous researchers have found that higher HbA1c was independently associated with advanced AAC scores, CAC risk, and CAC progression [ 10 12 ], however, they did not investigate the dose-response relationships between HbA1c and these outcomes. The current study showed a nearly linear dose-response relationships between HbA1c and AAC, which provided evidence for preventing AC through reducing HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the effects of HbA1c on AC, especially coronary artery calcification (CAC). The cross-sectional and longitudinal study showed that higher HbA1c is independently associated with advanced CAC progression among individuals with or without diabetes [ 10 , 11 ]. Previous studies have reported that CAC is rarely present without AAC, and AAC typically predates CAC [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large Korean cohort study showed an increased risk of CACS > 100 among patients with prediabetes, the prevalence being 12–31% higher than in subjects with normal fasting glucose. CAC progression was also more prominent in patients with prediabetes [ 30 ]. There is, however, diversity of opinion on this matter.…”
Section: Discussionmentioning
confidence: 99%